Applications of Ferrocenium Salts in Organic Synthesis - Toma, Štefan; Šebesta, Radovan (Synthesis, 2015)
Ferrocenium salts can be easily obtained from ferrocene by either synthetic preparation or in situ reaction. The ferrocenium ion can act as a one-electron oxidant and thus initiate or promote a range of radical processes. Ferrocene itself can donate electrons to suitable substrates, resulting in useful transformations. Ferrocenium salts can also act as mild Lewis acids. This paper highlights various uses of ferrocenium ions in organic reactions.1 Introduction2 Ferrocenium Salts as Lewis Acids3 Ferrocenium Salts as One-Electron Oxidants4 Ferrocene as an Electron Donor5 Catalysis with Other Ferrocenium Derivatives6 Conclusions
Keywords: catalysis; organometallic reagents; cations; ferrocene; ferrocenium